Pawn - Setianingrum, Nurul; Nur Hidayat; Taqwim, Rizky Insani; Rahmawati, Rini (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
Islamic gold pawning is a financing product that uses gold as collateral. With the convenience offered, gold pawn financing has its own risks, so sharia financial institutions that issue pawn products must mitigate risks. The implication is that the risks that arise can be minimized as early as possible. This research aims to mitigate risks at Baitul Maal Wattamwill (BMT) NU Ajung Jember Branch, East Java in minimizing risks arising from gold pawn financing. This study uses a qualitative research approach with a case study method. Data was collected in three ways, namely interviews, observation, and documentation. The data analysis technique was carried out in three stages, namely: data reduction, data display, and drawing conclusions and checking the validity of the data findings using source and method triangulation techniques. The results of this study state that risk management in gold pawning financing at Baitul Maal Wattamwill (BMT) NU East Java Ajung Jember Branch is carried out by identifying risks, determining policies to mitigate risks, and conducting risk monitoring and evaluation.